Transcriptome profiling reveals key regulatory factors and metabolic pathways associated with curd formation and development in broccoli - Zhu, Yinxia; Liu, Ce; Zhao, Mengyao; Duan, Yuxuan; Xie, Jingjing; Wang, Chunguo (Frontiers in Plant Science, 2024)
Broccoli, a cruciferous vegetable, has a unique indeterminate inflorescence structure known as curds. It is the main edible organ of broccoli and has a rich nutritional value and health benefits. However, the formation and development mechanism of the curd is still not well understood. In the present study, the shoot apical meristem (SAM) stage and three different development stages of curd (formation stage (FS), expansion stage (ES), and maturation stage (MS)) were identified and subjected to transcriptome sequencing to uncover the potential genes and regulatory networks involved in curd formation and development. The results indicated that the genes associated with the development of SAM such as BolAP1A, BolAP1C, BolCAL, and BolAGL6 play an important role in the abnormal differentiation of the curd apical buds. The genes, BolFRI, BolbHLH89, BolKAN4, BolAGL12, and BolAGL24, displayed significantly differential expression patterns in curd development may function in the regulation of the transition from inflorescence meristem (IM) to floral meristem (FM). Moreover, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of the differentially expressed genes (DEGs) indicate that phytohormones, such as auxin (AUX), gibberellins (GA), and abscisic acid (ABA) also play an important role in SAM proliferation and the transition from SAM to IM. In addition, the genes regulating photosynthetic reaction (BolLHCA1, BolLHCB1, BolPsbO, etc.) have a key involvement in the differentiation of secondary IMs during curd expansion. The genes associated with the metabolism of starch and sucrose (e.g., BolSPS4, BolBAM4) were significantly upregulated at the MS should contribute to the maturation of the curd. These findings provide new insights into the potential key regulatory factors and metabolic pathways involved in the formation and development of broccoli curds.